Big Data Support for Problem Solving Method in Mass Spectrometry Topic in Modern Analytical Chemistry Course - Muis, Irmayanti; Wonorahardjo, Surjani; Budiasih, Endang (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Extremely large and unpredictable user generation of data, all digitized and stored in large data repositories is built up by scientists, especially from modern analytical chemistry. This study aims to build a new approach in chemistry education, by utilizing Big Data sources to support IDEAL (I-Identify problem, D-Define goal, E-Explore possible strategies, A-anticipate outcomes and act, L-Look back and learn) Problem Solving learning model. Modern analytical chemistry studies and uses instruments to analize chemical compounds up to structural analysis. Modern instruments, such as mass spectrometer, generate information of compounds and stored in big data bank. This must be able to be accessed and used in chemistry education. This report would be around the benefits of using Big Data during learning process in this digital era, through IDEAL Problem Solving learning. Some preliminary progress would be presented. The growing number of data and resources would change also teaching and learning methodology in higher education. Some highlights about disruptive learning innovation would be described